Older adults can improve compensatory stepping with repeated postural perturbations - Dijkstra, Bauke W.; Horak, Fay B.; Kamsma, Yvo P. T.; Peterson, Daniel S. (Frontiers in Aging Neuroscience, 2015)
The ability to respond quickly and accurately to an external perturbation with a stepping response is critical to avoid falls and this ability is impaired in older, compared to young adults. However, little is known about whether young and older adults improve compensatory stepping responses similarly with practice. This study compares the extent to which young and older adults can improve, retain, and generalize postural compensatory steps in response to external perturbations. Centre of mass displacement, step characteristics and lower leg muscle activation latencies were measured during one training session of compensatory stepping in response to large surface translations in 13 young and 12 older adults. Retention was tested 24 hours later. Older adults decreased their centre of mass displacements over repeated exposure to large surface translations in both the anterior and posterior directions and retained these improvements. In contrast, young adults only showed adaptation and retention of forward stepping responses. Neither group was able to generalize improvements in stepping responses across directions. These results suggest step training may be beneficial for older adults, however additional, multidirectional training may be necessary to facilitate generalization of postural stepping responses for any direction of a slip or trip.